Teori Hudûd Muhammad Syahrur dan Kontribusinya dalam Penafsiran Al-Qur’an - Abdul Mustaqim (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
One of the great thinkers in the contemporary era is Muhammad Syahrûr, a Syrian liberal Islamic figure. Through his controversial works, al-Kitâb wal Qur’ân: Qirâ’ah Mu`âshirah, (al-Kitab and al-Qur’an: a Contemporary Reading) Syahrur introduces a new theory of Quranic interpretation, called as the theory of limits. He asserts that the theory of limits is an approach within ijtihad (individual interpretation) to study the muhkamât verses (clear and direct verses of law) of the Qur’an. The term limit (hudûd) used by Shahrur refers to the meaning of “the bounds or restrictions of God which should not be violated, contained in the dynamic, flexible, and elastic domain of ijtihad.”. By using the descriptive-analytical method, the article is talking about the contribution of the theory of limits in qur’anic interpretation that makes significant contributions to the enhancement of Qur’anic studies.